1956
DOI: 10.1161/01.cir.13.2.235
|View full text |Cite
|
Sign up to set email alerts
|

Arteriosclerosis in the Intramural and Extramural Portions of Coronary Arteries in the Human Heart

Abstract: Fifteen instances of intramural coronary arteries were observed in the dissection of 276 human hearts at consecutive unselected autopsies. All but 2 of these 15 had severe atheromata and narrowing of the lumina. It was thought important to determine whether or not the covering of the artery by cardiac muscle for a major part of its course protected the artery from atherosclerosis. From our data, one may assume that those portions surrounded by heart muscle were not protected from atherosclerotic process which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0
4

Year Published

1981
1981
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(57 citation statements)
references
References 0 publications
4
47
0
4
Order By: Relevance
“…[12] Although the condition is encountered by cardiovascular surgeons in approximately 15% of coronary bypass surgeries, it is reported that this rate fluctuates between 5% and 86% in autopsy studies. [13,14] A 0.99% prevalence of MB among patients who had undergone coronary angiography was determined in the present study, a finding similar to several others. [15] Prevalence has been reported as 0.5-2.5%.…”
Section: Discussionsupporting
confidence: 92%
“…[12] Although the condition is encountered by cardiovascular surgeons in approximately 15% of coronary bypass surgeries, it is reported that this rate fluctuates between 5% and 86% in autopsy studies. [13,14] A 0.99% prevalence of MB among patients who had undergone coronary angiography was determined in the present study, a finding similar to several others. [15] Prevalence has been reported as 0.5-2.5%.…”
Section: Discussionsupporting
confidence: 92%
“…5). While the incidence of myocardial bridges determined during autopsies is reported to be between 15-80%, it is shown to be between 0.5-2.5percent during angiography (Edwards et al 1956;Polachek 1961;Nobel et al 1976;Ishimori et al 1977;Voss et al 1980). A couple of factors generating this discrepancy can be accountable.…”
Section: Discussionmentioning
confidence: 99%
“…Its typical angiographic presentation is the systolic "milking" effect due to transient vascular compression. [1][2][3] The frequency of MB has been reported to range from 5.4 to 85% in autopsy series [4][5][6] and from 0.5 to 29.4% on coronary angiography. 1,[6][7][8][9][10][11] Although it remains to be determined how MB affects the cardiovascular system, MB has been associated with myocardial infarction [12][13][14][15][16][17] and sudden cardiac death, [18][19][20][21] and coronary spasm is thought to be one factor connecting cardiac events and MB.…”
Section: Introductionmentioning
confidence: 99%